Identification of a dual-function peptide for the detection and haematopoietic potency assessment of type I collagen hydrolysates - Guiya Deng; Jiajun Wang; Cuicui Men; Keyi Cao; Chengming Li; Liang Zheng; Haibin Liu; Shangwei Guo; Yaqin Huang (Collagen and Leather)
Abstract Type I collagen hydrolysate with haematopoietic activity has shown tremendous potential for application in the functional food fields. The identification of peptide with haematopoietic activity to ensure the efficiency of functional foods remains challenging because of the vast combinatorial potential of short peptides from collagen hydrolysates. In the present study, we identified a novel marker peptide (the I-1 peptide, GAAGLpGPK, p: hydroxyproline) for type I collagen with haematopoietic capabilities via theoretical sequence analysis and computational prediction of activity. The I-1 peptide was shown to increase the survival rate of haematopoietic stem cells following injury induced by 5-fluorouracil (5-FU), increasing the survival rate from 65.40 to 105.28%, thereby exhibiting significant haematopoietic activity. More importantly, the mechanism underlying the haematopoietic activity of the I-1 peptide was analogous to activate the JAK/STAT signalling pathway mediated by granulocyte‒macrophage colony‒stimulating factor. On this basis, a high-precision method for the detection of type I collagen hydrolysates was developed using the I-1 peptide (relative standard deviation = 1.57%). This study not only provides novel perspectives for the exploration of haematopoietic peptides but also offers a new methodology for controlling the bioactivity of collagen-based food products. Graphical Abstract